(3JhTjM GdOjHGL hMdjI GdEHJgGLs - (3HOQ GdOjf eMeO Hf jMji Hf YeQ Hf jhfS GdbQGais; (3GHf aQMhf , HQgGf GdOjf,J (B799 (3g` s ((3YKeGf Hf CMeO Hf eMeO YHO GdcQje GdOejQi s)
(3ChdgG (B:s
(3bGd GdeQMhe TjN GdESdGe eMeO GdeOYh HOQ GdOjf GdbQGai GdMeO ddg GdMi GdHGbi Ydi GdOhGe Gdbjhe GdPi dGQGO dCeQg s
(3BNQgG (B:s
(3hGddg SHMGfg hJYGdi hdi GdGfYGe hgh Gdehab ddeQGe hUdi Gddg hSde Ydi SjOfG hehdGfG GaVd GdNdb hYdi Bdg hUMHg GdcQGe s
(3hgh Pjd GdcJGH GdOjHGL GdePgH ai WHbGJ GdeGdcjIs
(3dGHf aQMhf hgPg GdfSNI eUMMI HNW eDdagGs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3JPjjds
Keywords: (3GdJGQjNs